The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s13048-019-0608-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y regulates proliferation and apoptosis in granulosa cells in a follicular stage-dependent manner

Abstract: Background: The complex regulatory mechanism involved in ovarian follicular development is not completely understood. Neuronal neuropeptide Y (NPY) is involved in the regulation of feeding behavior, energy homeostasis, and reproduction behavior, while its function in ovarian follicular development is not clear. The objective of this study was to investigate if and how NPY regulates follicle development in the ovary. Methods: All experiments were performed using Sprague Dawley rats. To understand NPY expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Moreover, NPY5R in granulosa cells varies among follicular stage and its response is strong at early antral (EA) stage. NPY5R regulates granulosa cell proliferation in a follicular stage-dependent manner, with an induction at EA and suppression at late antral follicles ( Urata et al, 2020 ). Conversely, NPY-induced increases in VEGF expression in 4T1 cells were attenuated only under Y5R antagonism ( Medeiros and Jackson, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NPY5R in granulosa cells varies among follicular stage and its response is strong at early antral (EA) stage. NPY5R regulates granulosa cell proliferation in a follicular stage-dependent manner, with an induction at EA and suppression at late antral follicles ( Urata et al, 2020 ). Conversely, NPY-induced increases in VEGF expression in 4T1 cells were attenuated only under Y5R antagonism ( Medeiros and Jackson, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking the NPY5R gene failed to prefer food odors over pheromones after fasting ( Horio and Liberles, 2021 ). Additionally, it was reported that NPY5R was involved in regulating the proliferation and apoptosis of granulosa cells ( Urata et al, 2020 ). More recently, NPY5R was found to be a molecular marker for tumorigenesis of HR (+)/HER2 (−) BC in adolescents and young adults ( Yi and Zhou, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…8). Genes examined that were putatively up-regulated by FSH glycoforms included: a) Phospholipase D1 ( Pld1 ), which encodes an enzyme implicated in a number of cellular pathways, including signal transduction mediated by GPCRs and receptor tyrosine kinases, subcellular trafficking, and regulation of mitosis [57]; b) Neuropeptide Y (NPY) receptor Y1 ( Npy1R ), which encodes for a GPCR involved in Npy-regulated granulosa cell proliferation and apoptosis [58, 59]; c) Antimüllerian hormone gene ( Amh ), encoding a glycoprotein belonging to the transforming growth factor beta superfamily, which is involved in follicular development [60]; and d) Vascular endothelial growth factor B ( Vegf-B ), a gene that encodes the VEGF-B protein, a factor involved in angiogenesis [61]. The FSH down-regulated gene examined was BCL2 like 1 ( Bcl2l1 ) which acts as anti-or pro-apoptotic regulators that are involved in a wide variety of cellular activities [62], including prolactin signaling [63].…”
Section: Resultsmentioning
confidence: 99%
“…Receptors of NPY, ghrelin, GLP‐1 and GIP among other gut hormones are present in the hypothalamus, pituitary, adrenal glands or ovaries of women. Expression of NPY and its receptors Y1, Y2, Y4 and Y5 have been reported in ovarian granulosa cells regulating their proliferation and apoptosis 63 . Ghrelin and its receptor GHSR‐1a are found in human and animal ovaries 64 .…”
Section: Gut Hormones In Infertilitymentioning
confidence: 99%